Multi-Locations Evaluation of Garden Pea Genotypes for Pod Characters and Yield - Luitel, Binod Prasad; Poudel, Krishna; Bhandari, Bishnu Bahadur (Nepalese Horticulture, 2023)
Pea genotypes developed by national breeding program exhibit wide geographical adaptation. To identify the best high yielding and wide adaptive genotypes, fourteen garden pea genotypes (13 improved and commercial) were studied for their phenotypic traits at two locations (Horticulture Research Station, Dailekh and Agriculture Research Station, Dhankuta) during 2018–2019. Field experiments were conducted at randomized complete block design with three replications in both locations. Combined analysis over the locations revealed that genotypes had highly significant (p ≤ 0.01) effect on pod length, pod diameter, seed number/pod, pod weight and fresh pod yield. HRSDGP-11-18-1 produced the highest (12.5 t/ha) fresh pod yield, followed by HRSDGP-11-18-11 (12.3 t/ha) and the lowest (8.2 t/ha) fresh yield was recorded in HRSDGP-11-18-9. HRSDGP-11-18-1 and HRSDGP-11-18-11 had 25.0 and 23.0% higher yield advantage over Sikkim Local variety, respectively. Pod length, pod diameter and seed number/plot were significantly (p ≤ 0.01), and positively correlated with fresh pod yield, and selection of these traits aid for the improvement of yield in garden pea genotypes. HRSDGP-11-18-1 and HRSDGP-11-18-11 were found superior at both locations and can be recommended to evaluate them at on-farm condition for further verification.